Unemployment amoung Young People in the Wielkopolska Labour Market - Kalinowska-Sufinowicz, Baha (Studia Oeconomica Posnaniensia, 2017)
The main goal of the paper is to present and assess the situation of young people in a regional perspective in comparison to Poland and other European Union countries in the years 2004-2015, with particular reference to the Wielkopolska Voivodeship. The paper defines the concept of young people, and then shows the problems that they face in the process of the transition between education and the labour market. The level of unemployment among young people and their share in the population of the unemployed total were the subject of interest in union, national and regional terms. Finally, the total situation of young people in Poland in comparison to the other EU countries was presented, and more specifically in the Wielkopolska region in the years 2004-2015.